FAO e-learning: major achievements of 2023 - Food and Agriculture Organization of the United Nations (Food and Agriculture Organization of the United Nations, 2024)
The FAO elearning Academy organized a series of successful international technical webinars in 2023, with over 3 000 participants and in collaboration with more than 50 partners worldwide. Last year, the FAO elearning Academy contributed to multiple events and conferences, and was very dynamic in its outreach strategy. Over 1 000 communication products were disseminated through various media and channels, including videos, press releases, articles, newsletters and publications. This cincludes a training course on silvolpastoralism.